Genome sequence of Burkholderia mimosarum strain LMG 23256(T), a Mimosa pigra microsymbiont from Anso, Taiwan - Willems, Anne (Michigan State University, 2013)
Burkholderia mimosarum strain LMG 23256(T) is an aerobic, motile, Gram-negative, non-spore-forming rod that can exist as a soil saprophyte or as a legume microsymbiont of Mimosa pigra (giant sensitive plant). LMG 23256(T) was isolated from a nodule recovered from the roots of the M. pigra growing in Anso, Taiwan. LMG 23256(T) is highly effective at fixing nitrogen with M. pigra. Here we describe the features of B. mimosarum strain LMG 23256(T), together with genome sequence information and its annotation. The 8,410,967 bp high-quality-draft genome is arranged into 268 scaffolds of 270 contigs containing 7,800 protein-coding genes and 85 RNA-only encoding genes, and is one of 100 rhizobial genomes sequenced as part of the DOE Joint Genome Institute 2010 Genomic Encyclopedia for Bacteria and Archaea-Root Nodule Bacteria (GEBA-RNB) project.